Cleavage of Toll-Like Receptor 9 Ectodomain Is Required for In Vivo Responses to Single Strand DNA - Fukui, Ryutaro; Yamamoto, Chikako; Matsumoto, Fumi; Onji, Masahiro; Shibata, Takuma; Murakami, Yusuke; Kanno, Atsuo; Hayashi, Takuto; Tanimura, Natsuko; Yoshida, Nobuaki; Miyake, Kensuke (Frontiers in Immunology, 2018)
Mouse Toll-like receptor 9 (TLR9) is an endosomal sensor for single-stranded DNA (ssDNA). TLR9 is transported from the ER to endolysosomes by a multiple transmembrane protein Unc93 homolog B1, and proteolytically cleaved at its ectodomain. The structure of TLR9 and its biochemical analyses have shown that the proteolytic cleavage of TLR9 ectodomain enables TLR9-dimerization and TLR9 activation. However, the requirement of TLR9 cleavage in vivo has not been studied. We here show that the 13 amino acids deletion at the cleavage site made TLR9 resistant to proteolytic cleavage. The deletion mutation in the Tlr9 gene impaired TLR9-dependent cytokine production in conventional dendritic cells from the mutant mice. Not only in vitro, in vivo production of inflammatory cytokines (TNF-α and IL-12p40), chemokine (CCR5/RANTES) and type I interferon (IFN-α) induced by administration of TLR9 ligand was also impaired. These results demonstrate that the TLR9 cleavage is required for TLR9 responses in vivo.